Kontribusi E-Puskesmas dan Integrasi LayananPrimer (ILP) terhadapInternal Service Quality dan Kepuasan Kerja yang dimoderasi oleh kompetensi SDM di Puskesmas Tebet - Awwalunisa Aprilia Wijaya; Hwihanus Hwihanus (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
The suboptimal level of patient satisfaction at Tebet Health Center underscores the necessity of enhancing Internal Service Quality (ISQ). This study aims to evaluate the contribution of E-Health (E-Puskesmas) and Primary Service Integration (ILP) toward ISQ and its subsequent impact on employee job satisfaction, while examining the moderating role of Human Resources (HR) competence. Employing a quantitative cross-sectional design, data were gathered from 100 employees through structured questionnaires, observations, and interviews. Data analysis utilized multiple linear regression and Moderated Regression Analysis (MRA). The findings reveal that partially, E-Puskesmas (p-value = 0.000; t_test = 4.409) and ILP (p-value = 0.000; t_test = 5.747) exert a significant positive influence on ISQ. Simultaneously, both variables significantly enhance ISQ (F_test = 31.108). Furthermore, this research identifies that HR competence acts as a significant moderator (p-value = 0.000; t_test = 5.221), strengthening the relationship between digital transformation, service integration, and internal quality. An improved ISQ is shown to directly increase employee job satisfaction (p-value = 0.000; t_test = 4.780). In conclusion, the synergy between technological adoption, systemic integration, and personnel competence is vital for optimizing internal performance and employee well-being at Tebet Health Center.